The Influence of Leadership Style and Work Environment on Soldier Performance With Work Discipline as an Intervening Variable (Case Study on Eskorta Ship Unit Command Fleet Ii) - Andi Abdul Aziz; Dedi Purwana; I Ketut R. Sudiardhita (JURNAL DINAMIKA MANAJEMEN DAN BISNIS, 2020)
This study aims to examine the effect of leadership style and work environment on soldiers who are mediated by work discipline. This study used a quantitative method by distributing questionnaires to 260 respondents who were KRI soldiers in the Fleet II Commando Eskorta Ship Unit. The data from the questionnaire were analyzed descriptively and quantitatively. Descriptive analysis is used to describe respondents' characteristics and research variables based on the questionnaire results. In contrast, quantitative analysis is carried out using Structural Equation Modeling (SEM) study with the AMOS and SPSS programs. Based on the results of SEM analysis, it is concluded that leadership style has no significant effect on work discipline. In contrast, the work environment has a positive impact on work discipline. The results further show that the work environment and work discipline have a positive effect on the performance of the soldiers. At the same time, the leadership style does not affect the performance of the soldiers. In further testing, the results of the mediation test using the Sobel test show that work discipline engagement can mediate the influence of leadership style and work environment on performance. This can indicate that an increase in leadership style and work environment can improve work discipline, which in turn will enhance the performance of soldiers. However, this research still needs to be developed by adding other variables and also expanding respondents or changing the object or place of study. Keywords: Leadership Style, Work Environment, Work Discipline, Soldier Performance, Structural Equation Modeling (SEM).